Implementasi Aplikasi Absen Siswa Pada SD Negeri 060944 - Safrizal; Adhar, Deni; Tanti, Lili; Ridho, Irdian (Publikasi Pengabdian Masyarakat, 2022)
The purpose of this community service activity is to increase the competence of teachers in the field of information technology in helping with daily work, namely the attendance process for students which can be done automatically using Microsoft Excel. Where previously in carrying out the attendance process the teachers still used the student attendance list book so that the recapitulation of the attendance list and making report cards still took a long time. The method of implementing PKM activities is carried out by surveying partner schools, preparation, training, mentoring and evaluating the results of PKM activities by distributing questionnaires. The results of the evaluation of PKM activities have an increasing impact of 85% on teacher competence in applying information technology, namely the use of Microsoft Excel in making student attendance which can be recapitulated automatically. This certainly gives the conclusion that the PKM training activities carried out by the PKM Team are very good..